FACTORS THAT INFLUENCE GROSS DOMESTIC PRODUCT IN OIL EXPORTING COUNTRIES MEMBERS OF THE ORGANIZATION OF ISLAMIC COOPERATION (OIC) IN THE PERIOD 1985-2016 - Imaduddin zakiy; Eko Fajar Cahyono (Universitas Airlangga, 2019)
The aim of this research is to analyze the impact of world oil prices, the dollar exchange rate, and inflation on economic growth in oil exporting countries at the organization of Islamic cooperation. The purposive sampling method used to Determine the 5 nation that fulfill the requirements needed. The Data used in this research is secondary Data Obtained from various international statistics institute. This study uses a quantitative approach and panel regression analysis of data that combines time series of data and crosssection data. The result of research with Fixed Effect estimation models shows that the impact of world oil prices, the dollar exchange rate, and inflation simultaneously have a significant effect on economic growth in oil exporting countries at the organization of Islamic cooperation. The other result shows that inflation partially does not have impact on economic growth in oil exporting countries at the organization of Islamic Cooperation, meanwhileother independent variables of the USD exchange rate and world oil prices partially have positive and significant effect on economic growth in oil exporting countries at the organization of Islamic cooperation during the period 1985-2016.